The Japanese Understanding on New Words with Suffix -Teki Across Generations - Teresa Angelina Kaluge (Lingua Cultura, 2020)
The research attempted to portray the language dynamic on using the suffix -teki among Japanese based on old and young generations as reflected by age. Data were collected by using questionnaires distributed to the Japanese native speakers. New words were responded to as understandable, doubtful, and difficult. Descriptive and inferential statistical analyses were used in order to find out the results. For both the young and old generations, the stem words from Kango were the easiest to understand, yet, the most difficult words were groups of Gairaigo, Wago, and Konshugo. A significant difference was found between the age groups. The old generation expressed more doubt on new foreign words than the young one only in using -teki for Gairaigo word group. It is concluded that some meanings of words with suffixes are understood across young and old generations. However, the development of technology and globalization may impact some doubtful responses that differentiate between these two generations.